Diagnosis and treatment of Rasmussen's encephalitis pose a big challenge: Two case reports and literature review. (August 2021) - Hammed, Ali; Badour, Maysaa; Baqla, Sameer; Amer, Fatema
Abstract: Rasmussen encephalitis (RE) is a rare disease of unknown etiology that causes severe chronic unihemispheric inflammatory disease of the central nervous system mainly in children. It leads to intractable seizures, cognitive decline and progressive neurological deficits in the affected hemisphere. We report two cases of RE, as defined by fulfillment of the 2005 Bien criteria. The diagnostic challenge of characterizing this rare disease will be highlighted by the extensive serum, CSF, MR imaging and EEG data in the two patients. In addition, we will review the various forms of therapy attempted in these two patients, namely anti-epileptic drug therapy and immunomodulatory therapy. Hemispherectomy was done for the second patient with favorable outcomes of controlling seizures, but unfortunately, he died because of meningitis. Until the causes of Rasmussen's encephalitis are known, it is difficult to anticipate how treatments will improve. Such a situation creates a therapeutic dilemma; hemispherectomy is not favored because of the inevitable postoperative functional deficits, but a real risk exists that treatments used to delay progression of the disease will defer definitive surgical treatment beyond the time when an optimum post-hemispherectomy outcome could be expected. Highlights: R asmussen encephalitis (RE) causes severe chronic unihemispheric inflammatory disease. RE should be suspected in any patient with refractory seizures. Its recognition is important because early intervention with surgery can improve outcomes.